Perilaku Berkendara Dampak Penerapan Electronic Traffic Law Enforcement (ETLE) Pada Simpang Bersinyal di Kota Pangkalpinang - Revy Safitri; Muhammad Fahri; Reza Arlianda (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2023)
Bangka Belitung Province is one of the provinces implementing ETLE to reduce the number of traffic violations. The implementation of ETLE in Bangka Belitung Province has been applied since March 2022 which has given an impact on changes in driver behavior. Driving behavior can be said to be the reaction of the driver/ rider to the environment when driving a vehicle. Based on previous research, it is known that driving behavior can be measured through the Driver Behavior Questionnaire (DBQ). Therefore, this study adopts DBQ to measure changes in driving behavior due to the implementation of ETLE in Pangkalpinang. This study aims to find out how the behavior of driver using the road after the application of Electronic Traffic Law Enforcement (ETLE) at signalized intersections in Pangkalpinang. The result indicates that driver/ rider “have almost never committed a violation by not wearing a safety belt while driving” and “have almost never using a cell phone while driving or when the vehicle is stopped at an intersection when the traffic light is red since the implementation of ETLE”. It can be concluded that the results of the analysis of violations recorded on ETLE are in line with the results of the analysis of driving behavior. However, further analysis is needed to determine the significant impact of implementing ETLE on driving behavior. The application of ETLE is expected to reduce violations that can trigger traffic accidents. Furthermore, the results of this study can be used as a basis for determining policies related to the transportation sector, especially improving traffic safety.